Unusual Esophageal Twin Foreign Body (Glass Marble) in a Neonate - Baldev Singh; Sanjeev Bhagat; Gaurav Kataria; Gurpreet Kaur; Ravinder Singh (Online Journal of Health & Allied Sciences, 2013)
Although ingestion of foreign body in oesophagus is common in pediatric age group, its occurrence in neonatal period is rare. Etiology behind these foreign bodies may be negligence or homicidal attempt for unwanted child. A high index of suspicion is required for diagnosis, whenever the neonate presents with symptoms related either to the respiratory or gastrointestinal tract. Delayed diagnosis can result in serious complications. We report a very unusual case of twin foreign body (glass marble) in oesophagus in a 30 days old female neonate. The peculiarity of this case concerns the unusual foreign body and age of the patient.